The Use of RADEC Learning Model on Student's Creative Thinking Skills through Social Studies Learning in Elementary School - Latif, Brilian Sejatining; Disman; Sopandi, Wahyu; Sujana, Atep (International Conference on Elementary Education, 2024)
This research was motivated by the low creative thinking skills in students in social studies learning in grade VI at one of the elementary schools in Garut Regency. This is due to the lack of creative stimulus provided in the school environment, the lack of interactive teaching models, and the lack of time and opportunities for students to easily explore. This study aims to analyze the creative thinking skills of grade VI learners after using the RADEC learning model. This study involved 18 students in one of the elementary schools in Garut Regency. The research method used is qualitative descriptive. The data collection used is observation, tests, and documentation studies. Data processing techniques use the Miles and Huberman techniques. This study obtained findings that at the read, answer, and create stages of creative thinking skills of students can be said to have appeared, at the discuss and explain stages of creative thinking skills of students can be said to have not appeared.